NMR spectroscopy of Cu(II) complexes with acrylamide and sodium acrylate copolymer and ω-amino acids - Kudryavsky, Dmitry L.; Fomina, Elena K.; Tychinskaya, Lyudmila Yu.; Skakovsky, Evgeny D.; Bogushevich, Svetlana E. (Journal of the Belarusian State University. Chemistry, 2021)
Macromolecular complexes of acrylamide and sodium acrylate copolymer with microelements, including Cu(II), may form at preparation of crop protection and stimulation compositions, where the copolymer serves as an adhesive, water-retaining and film-forming agent. Preparations for crop production may also contain amino acids that protect plants under stressful conditions (cold, dry, etc.). Carboxylic groups of copolymer, carboxylic and amino groups of amino acids may be involved in mixed Cu(II) ions complexes formation. Number of methylene groups separating carboxylic and amino group of amino acids affects its ability to form a stable chelate cycle and, therefore, ligand composition of mixed Cu(II) ions complexes with acrylamide and sodium acrylate copolymer and amino acid. This work is aimed at determining the ligand composition of mixed macromolecular Cu(II) ion complexes with acrylamide and sodium acrylate copolymer and ω-amino acids (β-alanine, γ-aminobutyric acid, ε-aminocaproic acid). 13C and 1H NMR spectroscopy was used to clarify complexes composition. A complex where carboxylic groups of amino acids are ligands has been found to form in aqueous solutions of Cu(II) ions and ω-amino acid (β-alanine, γ-aminobutyric acid, ε-aminocaproic acid) at molar ratio of Cu(II) ions – amino acid equal to 1 : 6. A chelate complex where both carboxylic and amino groups of β-alanine are involved in coordination has been discovered to form in the solution containing Cu(II) ions, β-alanine, as well as acrylamide and sodium acrylate copolymer at molar ratio of Cu(II) – β-alanine – copolymer COO− equal to 1 : 6 : 30. Carboxylic groups of copolymer participate in complex formation as well. Carboxylic groups of both amino acids and the copolymer have been shown to participate in complex formation in aqueous solutions containing Cu(II) ions, either γ-aminobutyric or ε-aminokaproic acid and also acrylamide and sodium acrylate copolymer.
Keywords: acrylamide and sodium acrylate copolymer; amino acids; macromolecular metal complexes; mixed complexes; Cu(II) ions; aqueous solutions